Lack of association between Toll-like receptor 2 polymorphisms and susceptibility to severe disease caused by Staphylococcus aureus. - Moore, C; Segal, S; Berendt, A; Hill, A; Day, N (2004)
To investigate a putative link between genetically determined variations in Toll-like receptor 2 (TLR2) and the occurrence of severe Staphylococcus aureus infection, the functional Arg753Gln single-nucleotide polymorphism and the GT repeat microsatellite in the TLR2 gene were examined in a large case-control study. No associations with disease or mortality attributable to these features were found.